Pendidikan Karakter pada Kitab Shahih Bukhari Muslim - Muhamad Wisnu; Neng Desti Ramadhani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Character education is a fundamental aspect in the formation of personality and noble morals for students. In the tradition of Islamic knowledge, the hadith of the Prophet SAW is one of the main sources in instilling moral and ethical values. The books of Sahih Bukhari and Sahih Muslim, as the two most authentic books of hadith, contain many teachings that are relevant to character education. This study aims to examine the values ​​of character education contained in selected hadiths from the two books. Using a qualitative approach and content analysis method, it was found that the hadiths in Sahih Bukhari and Muslim contain character values ​​such as honesty, responsibility, trustworthiness, empathy, discipline, and hard work. These values ​​are very relevant to be integrated into the modern education system in order to form a generation that is not only intellectually intelligent, but also morally and spiritually superior.